Pemanfaatan Adsorben dari Tongkol Jagung sebagai Karbon Aktif untuk Mengurangi Emisi Gas Buang Kendaraan Bermotor - Safri Gunawan; Hanapi Hasan; Ria Dini Wanty Lubis (Rekayasa Material, Manufaktur dan Energi, 2020)
This research utilizes corncob waste as activated carbon to be adsorbent. The objective of this research is to obtain the effect of corncob and sago powder as matrix composition in reducing vehicle exhaust gas emission. The composition used is 60 grams in every dough. It will be tested three times experimental which is 80:20, 70:30, 60:40 of corncob and sago powder variation of the composition, respectively. The result shows that the number of CO, HC, and CO2 decreases to 0.24%, 75.87%, and 5.9%, respectively. The conclusion from this research show that activated carbon from corncob greatly affect exhaust gas emissions in a vehicle.